2005
DOI: 10.1002/cbf.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patulin on thymus capillary of rats

Abstract: Patulin is a mycotoxin that is produced by species of Penicillum, Aspergillus, and Byssochylamys molds that may grow on a variety of foods including fruit, grains and cheese. Patulin, at a dose of 0.1 mg kg(-1) bw day(-1) was administered orally to growing male rats aged 5-6 weeks for a period of 60 or 90 days. The dose of patulin used in the present study was based on estimated human exposure levels. At the end of these periods, the thymus glands of patulin-treated and control Wistar rats were removed and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It is still unclear what role cellular organelles play in this process, but investigation of thymus cell ultrastructure may help. Earlier ultrastructural studies in patulin-treated rats showed degeneration of thymus capillary walls (34), apoptotic body formation, and cell apoptosis in interdigitating dendritic cells (35). Our study, too, suggests that T cell anomalies in patulin-treated rats lead to apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…It is still unclear what role cellular organelles play in this process, but investigation of thymus cell ultrastructure may help. Earlier ultrastructural studies in patulin-treated rats showed degeneration of thymus capillary walls (34), apoptotic body formation, and cell apoptosis in interdigitating dendritic cells (35). Our study, too, suggests that T cell anomalies in patulin-treated rats lead to apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…76 This group also showed the loss of the cytoplasm and mitochondrial cristae of cells, swollen endothelial cells, increased thickness of the basement membrane, closed lumen of capillaries, accumulation of the fibrous material at the periphery of the capillaries and nuclear anomalies in the walls of thymus capillaries. 77 PAT exposure leads to the reduced expression of IL-4, IL-13, IFN-gamma, IL-10 and intracellular GSH depletion in human peripheral blood mononuclear cells. 78 Patulin induced organ toxicity…”
Section: Immunotoxicitymentioning
confidence: 96%
“…At relatively high doses, it is actually toxic causing inflammation, ulceration, hemorrhage and have genotoxic, mutagenic, carcinogenic and teratogenic effects (Kawauchiya et al, 2011; Mahfoud et al, 2002). In addition to the immunotoxic effects (Escoula et al, 1988; Gül et al, 2006), it exhibits neurotoxic effects (World Health Organization, 1995) depending on the administered dose level. Based on a nitric oxide (NO) observable effect level (NOEL), the established maximum recommended concentration is 50 μg/L of patulin in apple juice, whereas the joint Food and Agriculture Organization/World Health Organization (WHO) expert committee on food additives (JEFCA) established a provisional maximum tolerable daily intake of 0.4 μg/kg body weight.…”
Section: Introductionmentioning
confidence: 99%